2002
DOI: 10.1097/00008877-200209000-00018
|View full text |Cite
|
Sign up to set email alerts
|

SR141716, a central cannabinoid (CB1) receptor antagonist, blocks the motivational and dopamine-releasing effects of nicotine in rats

Abstract: The central CB(1) cannabinoid receptor has recently been implicated in brain reward function. In the present study we evaluated first the effects of the selective CB(1) receptor antagonist, SR141716, on the motivational effects of nicotine in the rat. Administration of SR141716 (0.3 and 1 mg/kg) decreased nicotine self-administration (0.03 mg/kg/injection). SR141716 (0.3-3 mg/kg) neither substituted for nicotine nor antagonized the nicotine cue in a nicotine discrimination procedure, but dose-dependently (0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
298
2
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 377 publications
(333 citation statements)
references
References 70 publications
19
298
2
7
Order By: Relevance
“…), reduced nicotine self-administration in rats (Cohen et al, 2002). Here, we report that rimonabant (1 mg/kg, i.p.)…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…), reduced nicotine self-administration in rats (Cohen et al, 2002). Here, we report that rimonabant (1 mg/kg, i.p.)…”
Section: Discussionmentioning
confidence: 62%
“…In a previous study, we have identified mesolimbic dopaminergic transmission as a possible neurochemical substrate of rimonabant-induced reduction of nicotine selfadministration (Cohen et al, 2002). Indeed, rimonabant reduced the dopamine-releasing effects of nicotine as assessed by brain microdialysis and drug discrimination.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations